Pemahaman Syukur Dengan Self-Esteem Rendah Pada Mahasiswa Tasawuf dan Psikoterapi UIN Raden Intan Lampung - Natasha Aura Lintang Jaya; Agung M. Iqbal; Nesia Mu’asyara (Jurnal Riset Rumpun Agama dan Filsafat, 2025)
This research is motivated by the phenomenon of low self-esteem experienced by some students of Sufism and Psychotherapy at UIN Raden Intan Lampung, particularly due to feelings of insecurity regarding their physical appearance. This condition often stems from a lack of self-confidence that arises from the beginning, especially related to the chosen study program. Students who feel insecure about their academic choices tend to experience feelings of insecurity that impact various aspects of life, particularly physical appearance. They feel different and less confident, which ultimately affects their self-acceptance and self-esteem. Consequently, this condition contributes to a decline in low self-esteem. The method used is descriptive qualitative, with data collection through observation, in-depth interviews, and questionnaires. Participants were selected using purposive sampling based on criteria of low self-esteem related to feelings of insecurity about appearance. The results of the study indicate that the understanding of gratitude is not merely an expression of outward thanks, but it forms a deep inner awareness of divine wisdom in various circumstances. Students who internalize the understanding of gratitude tend to be more capable of self-acceptance, reducing feelings of insecurity, and building a positive outlook on their existence. The understanding of gratitude strengthens inner peace, enhances self-confidence, and motivates comprehensive self-improvement. These findings affirm that the understanding of gratitude is an effective spiritual approach to addressing low self-esteem and can serve as a relevant mentoring model for students.